Revealing rate‐limiting steps in complex disease biology: The crucial importance of studying rare, extreme‐phenotype families. (8th April 2016) - Chakravarti, Aravinda; Turner, Tychele N.
Abstract : The major challenge in complex disease genetics is to understand the fundamental features of this complexity and why functional alterations at multiple independent genes conspire to lead to an abnormal phenotype. We hypothesize that the various genes involved are all functionally united through gene regulatory networks (GRN), and that mutant phenotypes arise from the consequent perturbation of one or more rate‐limiting steps that affect the function of the entire GRN. Understanding a complex phenotype thus entails unraveling the details of each GRN, namely, the transcription factors that bind to cis regulatory elements affected by sequence variants altering transcription of specific genes, and their mutual feedback relationships. These GRNs can be identified through their rate‐limiting steps and are best uncovered by genomic analyses of rare, extreme phenotype families, thus providing a coherent molecular basis to complex traits and disorders. Abstract : Gene regulatory network and its postulated effects on a binary phenotype which is sex‐dependent. Phenotype altering variants in a rate‐limiting (with respect to GRN activity) gene ( X ), in contrast to others (A, B, C), will affect the group with the higher trait values because they will have larger impact.